Properties of Electrochromic Cell with WO3 and NiO: the Influence of Ionic Conductor - Sabov, T.N.; Hatsevych, I.M.; Gudimenko, O.I.; Melnyk, V.P.; Romanyuk, B.M.; Telega, V.M.; Nikirin, V.A. (Physics and Chemistry of Solid State, 2015)
The electrochromic WO3 and NiO films were deposited by magnetron sputtering on indium tin oxides coated glass. The structural properties of the films were investigated by scanning electron microscopy and X-ray diffractometery techniques. The electrochromic properties of the films were investigated by means cyclic voltammetry using different types of ionic conductors. The use of water electrolytes and electrolytes which are based on propylene carbonate leads to the destruction of electrochromic cells. The stable working electrochromic cell with WO3 and NiO films was obtained using ionic liquid as the ionic conductor. The coloration efficiency of electrochromic cell which is based on amorphous WO3 film and crystalline NiO film is 28.7 cm2/C.